Pengaruh Aplikasi Tiktok Terhadap Akhlak Remaja Muslim di Pulo Brayan Darat I Kecamatan Medan Timur - Akhbari, Luthfi (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2023)
Find out and understand the influence of the Tiktok application platform technology on the morals of Muslim youth. Rapid technological developments bring major changes in human life both from a social and cultural perspective, but technology in the form of social media aims to provide convenience in terms of communication so that it has an impact on users, both positive and negative perceptions. One of the technology platforms is social media in the form of the Tiktok application which is currently popular and in demand by all groups, from children to adults. The purpose of this study was to determine the effect of Tiktok application users on morals among Muslim teenagers.Keywords: The Influence of TikTok, The Impact of TikTok on Teen Morals.